Effect of Single Dose Intramuscular Methylprednisolone Injection into the Masseter Muscle on the Surgical Extraction of Impacted Lower Third Molars: a Randomized Controlled Trial - Vyas, N; Agarwal, S; Shah, N; Patel, D; Aapaliya, P (Kathmandu University Medical Journal, 2015)
Background Lower impacted third molar surgical extraction usually causes post-surgical sequelae like pain, trismus and swelling as a result of postoperative inflammatory response. Objective The aim of this study was to evaluate and compare the efficacy of single dose 40-mg (1cc) of methylprednisolone acetate, injected into the masseter muscle, preoperatively one hour before the surgery or post-operatively, immediately following the surgical removal of impacted lower third molars, in controlling most common postoperative sequelae, i.e. trismus, pain and swelling of facial soft tissue. Methods A randomized control study was done of 60 patients. Each patient was categorized in two groups, group I and group II, according to the time of receiving methylprednisolone acetate. Group I was injected 40mg of methylprednisolone acetate into the masseter muscle via the intrabuccal approach, one hour before the surgery. Group II was injected 40mg of methylprednisolone acetate into the masseter muscle via the intrabuccal approach, immediately after suturing of the surgical wound. The washout period was one month after the first operation. Evaluation were made of postoperative pain, trismus and swelling. The numeric pain scale (NPS) was used for pain assessment. Results When the patients were administered methylprednisolone acetate preoperatively, showed superior results in terms of oral aperture, pain and all the facial swelling parameters, with statistically significant differences versus the postoperatively administered methylprednisolone acetate (p < 0.05). Conclusions A single dose of 40 mg (1cc) methylprednisolone acetate injected into the masseter muscle preoperatively is more effective in reducing pain, trismus and swelling, when compared to that administered postoperatively. Kathmandu University Medical Journal Vol.12(1) 2014: 4-8